Audit Sistem Akademik Terhadap Akurasi Data Mahasiswa Universitas XXX dengan Framework COBIT 4.1 - Juniar Wibowo, Yehezkiel; Dharmawan, Alexander; Wahyuni, Ana (Institut Teknologi Garut, 2025)
This study aims to evaluate and provide recommendations for improvements to IT governance in the Integrated Information System (SISTA) at XXX University, using the COBIT 4.1 standard with domains AI2, AI7, DS5, DS10, DS11, ME1, and ME2. This study uses a literature review method and data collection by distributing questionnaires to 6 respondents consisting of PUSTIK staff and lecturers. The results of the data collection show the maturity level of each domain. The AI domain score was 3.4, which is at the Defined level, DS was 2.7 at the Repeatable but Intuitive level, and ME was 2.7 at the Repeatable but Intuitive level. Based on the analysis of the maturity level results, recommendations for improvement are needed to improve IT governance in SISTA at XXX University in order to improve its quality.